2011
DOI: 10.1111/j.1440-1754.2011.02103.x
|View full text |Cite
|
Sign up to set email alerts
|

Vincristine pharmacodynamics and pharmacogenetics in children with cancer: A limited‐sampling, population modelling approach

Abstract: No correlation was identified between vincristine clearance, vincristine neurotoxicity, age, sex or concomitant steroid therapy. The limited sampling methodology proved acceptable to patients and families and would be suitable for larger scale studies including a wider range of genotypic variants and more detailed prospective evaluation of neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…This is further supported by the high volume of distribution (1.76 L/kg) suggesting extensive tissue uptake of vincristine. The elimination half-life in the Tasmanian devil (approximately 11 h) is similar to adult and infant humans [19], [31], [32]. Plasma clearance of vincristine would have been expected to be more rapid than that observed in humans if rapid elimination of the drug played a role in their resistance to toxicity.…”
Section: Discussionmentioning
confidence: 89%
“…This is further supported by the high volume of distribution (1.76 L/kg) suggesting extensive tissue uptake of vincristine. The elimination half-life in the Tasmanian devil (approximately 11 h) is similar to adult and infant humans [19], [31], [32]. Plasma clearance of vincristine would have been expected to be more rapid than that observed in humans if rapid elimination of the drug played a role in their resistance to toxicity.…”
Section: Discussionmentioning
confidence: 89%
“…The effects of CYP3A5*3 on treatment outcomes were possibly a result of its involvement in vincristine metabolism rather than CPA metabolism. It has been demonstrated that CYP3A5 promotes the loss of the parent drug and formation of the major metabolite of vincristine, M1, in the liver . Doxorubicin has been reported to be an inhibitor, but not a substrate, of CYP3A.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be achieved by a lower ratio of vincristine to its’ primary metabolite (M1) [88]. Despite these intriguing results, two other studies, which enrolled a total of 86 patients, and evaluated the presence of CYP3A5*3 , CYP3A5*6 and ABCB1 SNPs failed to confirm a significant association with the occurrence of vincristine-induced side effects [8991]. These studies are limited due to the small number of patients included.…”
Section: Vincristinementioning
confidence: 99%